A Case of Systemic Lupus Erythematosus Presenting with the Clinical Picture of Recurrent Cerebral Venous Thrombosis and Devic-Like Syndrome - Şule Bilen; Cevdet Şahin; Erdem Gürkaş; Gürdal Orhan; Fikri Ak (Türk Nöroloji Dergisi, 2011)
Systemic lupus erythematosus(SLE) which is generally related to central or peripheral nervous system abnormality is a complex and multisystem involving disease. Neurological involvement in SLE is known as bad prognostic criteria and considered as the major cause of mortality. 27 year old female patient was admitted to our clinic with the clinical pictures of recurrent cerebral venous thrombosis and myelitis accompanying to optic nerve involvement. While she has been evaluated for the etiology she was diagnosed as systemic lupus erythematosus because of establishment of the antibodies ANA ve Anti SS-A. Her response to endoxan and steroid treatment was good.In this paper we aimed to emphasize the significances of consideration of the diagnosis of SLE and immediate and appropriate immunosupressive treatment in patients applying in the clinical pictures of cerebral venous thrombosis and myelitis with optic nerve involvement eventhough they do not have the cardinal symptoms of the disease